Evaluation of the smear layer removal ability of passive ultrasonic irrigation - Le, Thi Thu Nga; Phan, Anh Chi (Tạp chí Y Dược Huế, 2025)
Background: The smear layer can prevent the penetration of intracanal medicaments into dentinal tubules and influence the adaptation of filling materials to canal walls. Passive ultrasonic irrigation is one of methods to removing smear layer. The purpose of this study is to compare the smear layer removal ability between Passive ultrasonic irrigation and Conventional needle irrigation. Materials and Methods: 30 extracted human premolar roots were selected and randomly divided into 2 groups (n=15) based on root canal irrigation methods with 17% EDTA solution: (1) Conventional needle irrigation, (2) Passive ultrasonic irrigation. The roots were prepared with Reciproc Blue 25 file and was removed smear layer by 2 different methods of irrigation. The study sample was then sectioned longitudinally with a diamond cutting disc, randomly selecting half of the root. After undergoing sample processing, the half roots were observed and evaluated for the presence of smear layer under a scanning electron microscope with a magnification of 1000 times according to Torabinejad (2003). Results: In both groups, mean of smear layer score in apical higher than that in cervical (p>0.05). There is no difference in mean of smear layer score between 2 groups at the apical, middle and cervical. Conclusion: Passive ultrasonic irrigation is as effective in removing smear layer as Conventional needle irrigation.